2019
DOI: 10.13057/biodiv/d201003
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Selection of doubled haploid lines of rainfed lowland rice in preliminary yield trial

Abstract: Abstract. Akbar MR, Purwoko BS, Dewi IS, Suwarno WB, Sugiyanta. 2019. Short Communication: Selection of doubled haploid lines of rainfed lowland rice in preliminary yield trial. Biodiversitas 20: 2796-2801. Yield trial is an important step in rice breeding program. This research was aimed at evaluating agronomic characters and selecting the best doubled haploid rainfed rice lines for next advanced yield trial. An experiment was conducted in Indramayu from March to August 2017. The research was arranged in rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 15 publications
7
21
0
Order By: Relevance
“…Meanwhile, the characters influenced by genotype and environmental interactions were plant height, the height of ear cobs, number of green leaves, male flowering days, female flowering days, anthesis silking interval, diameter of cob, number of grains per cob row, weight of harvested cob, yield, productivity, and weight of 1000 seed. The apparent interaction variances showed that the differences in responses between tolerant and sensitive genotypes to environmental differences (Ali et al 2015;Safitri et al 2016), which becomes the fundamental basis in the selection of secondary characters (Al-Naggar et al 2015;Anshori et al 2019;Akbar et al 2019). Therefore, significant characters to interactions variance were continued for the next analysis in determining secondary characters that are adaptive to drought stress.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, the characters influenced by genotype and environmental interactions were plant height, the height of ear cobs, number of green leaves, male flowering days, female flowering days, anthesis silking interval, diameter of cob, number of grains per cob row, weight of harvested cob, yield, productivity, and weight of 1000 seed. The apparent interaction variances showed that the differences in responses between tolerant and sensitive genotypes to environmental differences (Ali et al 2015;Safitri et al 2016), which becomes the fundamental basis in the selection of secondary characters (Al-Naggar et al 2015;Anshori et al 2019;Akbar et al 2019). Therefore, significant characters to interactions variance were continued for the next analysis in determining secondary characters that are adaptive to drought stress.…”
Section: Resultsmentioning
confidence: 99%
“…To generate the adaptive corn variety, many corn genotypes must be selected and grown under normal and stress condition in order to evaluate their responses to those conditions properly and effectively. This concept is widely applied by Anshori et al (2019) and Anshori et al (2020) on rice under salinity stress, Akbar et al (2019) and Farid and Ridwan (2018) on rice under drought stress, Adhikari et al (2019); Sah et al (2020) and Badr et al (2020) on corn under drought.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the results of the PCA, PC1 in all character groups had a high proportion variance (PV) value, i.e., above 70%. According to Mattjik et al (2011), Rehman et al (2019, Akbar et al (2019) and Anshori et al (2019), optimizing the representative PC assessment is based on the cumulative proportion which reaches 0.8. By seeing the comparison of the PC1, PV value against the CP standard, the use of PC1 as the basis for the selection index was considered sufficient to represent the variance of tolerance properties.…”
Section: Discussionmentioning
confidence: 99%